Pengembangan Sistem Informasi Akuntansi PT. Surya Warfa Kharisma Studi Kasus: Penjulan, Piutang, dan Penerimaan Kas - Darudiato, Suparto; Sari, Effie Cendana (ComTech: Computer, Mathematics and Engineering Applications, 2011)
To increase sales, the management and sales department requires accurate, relevant and up-to-date information to support its function. Currently the amount of outstanding accounts receivables becomes one of the obstacles. So, credit limits criteria are applied as one of the effort to emphasis the outstanding receivables. Surely it will have an impact on increasing the effectiveness and efficiency of operations and ultimately will enhance the competitiveness. This research was done in three stages, data collection, analyzing the system requirements of current system to synergy with company?s target, and the results of needs analysis are developed into a new accounting information system with object-oriented approach and UML diagrams.